Effective Management of School Administrative Personnel in an Effort to Improve Services - Lumungga, Mahda Iza; Mustiningsih, Mustiningsih; Bafadal, Ibrahim (Universitas Negeri Malang, 2024)
The management of administrative personnel in a school is a key aspect in determining the efficiency, effectiveness, and quality of educational services. The purpose of this study is to provide an overview of the effective management of school administrative personnel to be implemented, while containing a discussion of: (1) effective management of school administrative management; (2) the process of managing school administrative personnel; (3) efforts to improve administrative services in schools/madrasas. This research uses qualitative methods with literature study techniques through previous studies and literature related to the topic of the research. The results showed that administrative management carried out by administrative staff in schools/madrasas is still not in accordance with the Regulation of the Minister of National Education No. 24 of 2008 on School Administrative Staff Standards. For this reason, effective management of school administrative personnel is needed to improve administrative services in schools/madrasas. The effective management of school administrative personnel includes planning, recruitment and selection, training and development, performance management, technology in administrative management, and evaluation.